“My Family’s Weight on My Shoulders”: Experiences of Jewish Immigrant Women from the Former Soviet Union (FSU) in Toronto - Marina Morgenshtern (Social Sciences, 2019)
In dominant western society, we tend to interpret the experiences of immigrant women as emancipation and liberation, rather than as the complex experiences of subjects acting within several hegemonic systems. While intersectional and transnational feminism led to questioning this view through the discussion of the challenges faced by immigrant women from developing countries, their counterparts from socialist countries have been largely ignored. To address this gap, this article focuses on the employment and social reproduction experiences of 11 white, professional, heterosexual, immigrant Jewish women from the former Soviet Union (FSU) who are now living in Toronto, Canada. The data used in this article was collected as part of a study on lived experiences of Jewish immigrant couples from FSU in Toronto. This study utilized intersectional feminist analysis as a theoretical framework and combined the qualitative methodologies of Testimonio and Oral History. This data suggests that, for these women, immigration had mixed outcomes. Although the material conditions of their lives may have changed, the traditional moral associations between femininity, domesticity, and maternity remained strong. Apparent heterosexual privilege both challenged and reinforced their subordination, in that it facilitated their access to Canadian education and professional jobs and promoted their social legitimacy/status, while also resulting in greater subordination at work and home where they had more tasks to fulfill than in premigration life. These findings challenge the monolithic representation of immigrant women’s experience and enhance our ability to generate a more comprehensive theory of those experiences.